Anthocyanin Biosynthesis and Degradation Mechanisms in Solanaceous Vegetables: A Review - Liu, Ying; Tikunov, Yury; Schouten, Rob E.; Marcelis, Leo F. M.; Visser, Richard G. F.; Bovy, Arnaud (Frontiers in Chemistry, 2018)
Anthocyanins are a group of polyphenolic pigments that are ubiquitously found in the plant kingdom. In plants, anthocyanins play a role not only in reproduction, by attracting pollinators and seed dispersers, but also in protection against various abiotic and biotic stresses. There is accumulating evidence that anthocyanins have health-promoting properties, which makes anthocyanin metabolism an interesting target for breeders and researchers. In this review, the state of the art knowledge concerning anthocyanins in the Solanaceous vegetables, i.e. pepper, tomato, eggplant and potato, is discussed, including biochemistry and biological function of anthocyanins, as well as their genetic and environmental regulation. Anthocyanin accumulation is determined by the balance between biosynthesis and degradation. Although the anthocyanin biosynthetic pathway has been well studied in Solanaceous vegetables, more research is needed on the inhibition of biosynthesis and, in particular, the anthocyanin degradation mechanisms if we want to control anthocyanin content of Solanaceous vegetables. In addition, anthocyanin metabolism is distinctly affected by environmental conditions, but the molecular regulation of these effects is poorly understood. Existing knowledge is summarized and current gaps in our understanding are highlighted and discussed, to create opportunities for the development of anthocyanin-rich crops through breeding and environmental management.